In situ experiments with synchrotron high-energy x-rays of Ni-Ti alloys produced by powder metallurgy - Neves, Filipe (2013)
The structural evolution that takes place during the homogenization heat treatments of powder metallurgical Ni-Ti- alloys was studied by in situ synchrotron diffraction. It is proposed to get a deeper understanding of this phenomenon by using different types of thermal/mechanical cycles.